Cardiovascular Risk In Patients With Systemic Sclerodermia - Saidova Mukhabbat Mukhidinovna; Khamroeva Yulduz Saidovna (International Journal on Orange Technologies, 2021)
The frequency and features of clinical manifestations of diseases of the cardiovascular system in patients with systemic scleroderma (SSD) are analyzed. The study included 55 patients aged 35 to 60 years who were diagnosed with SSD. Cardiovascular risk was studied using the SCORE scale, as well as instrumental methods of ECG and Echocardiography. Among the surveyed, a high incidence of cardiovascular diseases was noted. However, subjective complaints were relatively rare. According to ECG data, 74.5% of patients with SSD had pathological symptoms, including ischemic changes in 46.3% of patients. Acute cardiovascular events (MI and OSN) were registered in 15 of the main groups, which accounted for 27.3% of the total number of patients with SSD. The results obtained showed that lesions of the cardiovascular system in patients with SSD show low severity of symptoms